RED BRICKS AND LIGHT BRICKS COST ANALYSIS FOR WALLS AND MILD STEEL AND WOOD FOR ROOF TRUSS ( BPN office construction case study in Mojokerto regency) - Puri, Wuwuh Asrining (EXTRAPOLASI: Jurnal Teknik Sipil, 2013)
The fast growth of infrastructure requires the need of advance science and technology. Moreover, thedevelopment of building materials recently are more advanced, begin from replacement brick with light brickor floor plat replaced with lightweight cover, the metal deck, then a roof that no longer use an easel tripod,the lightweight steel roof truss. To compare the economic value of the current building materials, it needs astudy on the material and installation price comparisons; for wall, it needs the comparison on the brickmaterials and lightweight brick, as both materials have many advantages and are easy in installment. Thisstudy is also to analyze the cost of wood frame construction and roof construction price of mild steel frame /Truss in buildings that are commonly used, and finally, to compare the costs of each structure from bothmaterials. The study on BPN office Mojokerto regency finds that the consumption of the brick wall materialis much cheaper Rp 30.386, - per m2 or Rp. 169.184.690, for all building wall compared with theconsumption of lightweight brick. Whereas the wooden roof frame is cheaper Rp 11.349.724 , - for all roofframe building compared with the material of mild steel / truss . This study focuses on the cost of materialsand installation. Other costs and Installation time of both types of materials are not analysed.Keywords : cost, red brick, light brick, mild steel,wood